Mastering the art of sectioning: a comprehensive guide to slide-microtome technology and histological applications - Abd El-Aziz, Yasmin M.; Sobh, Mohammed S.; Saad, Hebatallah M.; Morsy, Menna H. E.; El-Haroun, Ehab; Abass, Kasim Sakran; Abdul Kari, Zulhisyam; Mathew, Roshmon Thomas; Eissa, Moaheda E. H.; Eissa, El-Sayed Hemdan (Frontiers in Veterinary Science, 2025)
The well-known technique of microtomy, which is an essential cutting tool, was first developed for light and transmission electron microscope uses, but it is currently also utilized to prepare specimens for atomic force microscopy (AFM), ion microscopy using a focused ion beam (FIB), and scanning electron microscopy (SEM). Ultramicrotomy can only be used on soft substances and metals that are sufficiently ductile to be cut with a diamond knife. Before being sliced by a microtome, many soft materials must first go through numerous preparatory processes. The choice of microtome type and blade material depends on the specimen being cut and the desired thickness of the sections. The scope of this review is to provide an overview of the main types of microtomes and a comparison between various common types of microtomes, recognizing and classifying frequent difficulties in tissue sample preparation with a particular emphasis on sectioning and staining problems. This review will put your focus on some problems, such as thick section borders, prolonged fixation or excess aldehyde concentration, low ethanol concentration or incomplete fixation, and sections not sticking to slides, especially during staining. In addition, explaining the artifacts during the processing of specimens using a microtome along with discussing the applications, calibration, maintenance of the microtome, as well as its troubleshooting, in addition to future trends, as well as challenges for this tool. Studying these issues will elevate key insights regarding the necessity of exact fixation, temperature control, accurate sectioning techniques, and gentle handling of tissues for the quality of histological samples used for microscopic studies.